Analisis Titik Kritis Keharaman Produk Tutug Oncom - Lutfi Yulmiftiyanto Nurhamzah; Nisatami Husnul; Mufti Ghaffar (Universitas Djuanda, 2025)
Food producers' readiness for halal certification needs to pay attention to many aspects. Tutug oncom is a product made from oncom which is made from peanut meal, then fermented for 7 days using Rhizopus sp. This research aims to determine the critical point for harmfulness of tutug oncom. Data was collected by conducting observations, interviews with producers, and documentation, as well as making adjustments to the halal-related guidelines that apply in Indonesia. The results of this research are: 1) oncom raw materials are the critical point of haram because they do not have a halal certificate, especially since oncom uses bacterial culture during the fermentation process, 2) sautéing and roasting are the critical points of haram in the production process, because there are several other spices that are not yet guaranteed halal, 3) no critical points are found on production equipment, this is because the equipment is kept in a clean, closed condition, and is always replaced if something is broken. Based on the results of our research, it shows that foods that are commonly consumed daily may have the potential to have a critical point for harmfulness both in the ingredients and the processing process.